Efeito do tratamento da apneia obstrutiva do sono de grau leve, sobre a qualidade ee vida, humor e atenção sustentada: estudo randomizado, paralelo, simples cego e controlado - Luz, Gabriela Costa Pontes [UNIFESP] (2017)
Introduction: The effect of Continuous Positive Airway Pressure (CPAP) or Oral Appliance (OA) treatment on obstructive sleep apnea (OSA) in the domains of quality of life, mood and cognition is still controversial and especially in mild OSA. Objective: To evaluate and compare the effect of treatment with CPAP and OA in patients with mild OSA in improving quality of life, mood and sustained attention. Methods: Patients of both genders were included; body mass index (BMI) ≤ 35 kg /m2; age between 18 and 65 years; diagnosis of mild OSA - apnea and hypopnea index (AHI) ≥ 5 events per hour of sleep and ≤ 15 events per hour of sleep independent of the presence of excessive daytime sleepiness (EDS), but with at least one sign and/or symptom and with a minimum mandibular protrusion of 7mm. Patients were randomly assigned to 3 groups: group 1 - CPAP, group 2 - OA and group 3 - control without treatment. The patients were submitted to two evaluations: baseline and after 6 months of treatment. The subjects performed the following procedures in these evaluations: Pittsburgh Sleep Quality Index (PSQI), physical examination, otorhinolaryngological examination, baseline polysomnography (PSG) (and using CPAP in group 1), Epworth Sleepiness Scale (ESS), Beck Anxiety and Depression Inventories (BAI and BDI), Functional Outcomes of Sleep Questionnaire (FOSQ) and 5 measures of Psychomotor Vigilance Task (PVT). For statistical analysis, we used a descriptive analysis (means ± standard deviation) and for assessment of the groups at different times we used General Linear Model (GLM). Results: 48 patients participated in the study, 15 in group 1, 15 in group 2 and 18 in group 3. Regarding the PSG, we observed better results in several variables, after six months of treatment in group 1, compared to groups 2 and 3. No differences between groups were observed in ESS, PSQI, BAI and BDI. Regarding FOSQ, we observed that group 1 presented improvement in the followings domains: general productivity; social outcomes and overall mean, when compared to the other groups. Regarding PVT, we observed no difference between the groups. Adherence to OA was higher when compared to CPAP. Conclusion: CPAP was the best intervention for normalization of polysomnographic parameters and improvement of quality of life. There was no difference in mood and sustained attention between treatments. The OA showed greater adherence than CPAP during the six months of treatment.